Child-Friendly School in Building Students Character: A Literature Review - Elsy Triyana; Hasan Hariri; Riswanti Rini; Sowiyah Sowiyah (Universitas Muhammadiyah Enrekang, 2022)
Nowadays, many students are still lack of good character and there should be a character-building program from school. This paper aimed to collect and analyze articles that are related to the implementation of a Child-Friendly School in building students' characters. The method used was a literature review, in which articles were collected from Google Scholar and the Directory of Open Access Journals. The criteria of articles used were from the last five years. Based on the articles that were collected, it can be concluded that Child-Friendly School is a very good educational concept to be implemented especially in building students' character.